Transformasi Menuju Pelayanan Publik Berkualitas di Era Digital - Erinaldi, Erinaldi (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
In the ever-evolving digital era, the implementation of digital technology has become crucial in enhancing the efficiency and effectiveness of public services across various nations and regions. This article discusses the role of digital technology in the transformation of bureaucracy, with a focus on e-government approaches and other digital technology initiatives. Through document analysis and case studies, this article explores various approaches, strategies, and challenges associated with the adoption of digital technology in bureaucracy. Findings indicate that while digital technology offers significant potential for improving public services, its adoption also presents several challenges, such as data security issues, limitations in technology infrastructure, resistance to change, and financial constraints. To address these challenges, a holistic and integrated approach is required, considering technical aspects, organizational culture, policies, and finances. By overcoming these challenges, governments can leverage digital technology optimally to enhance public services and meet societal expectations in the continuously evolving digital age.